Advancing Slope Stability and Hydrological Solutions Through Biocementation: A Bibliometric Review - Armstrong Ighodalo Omoregie; Tariq Ouahbi; Fock-Kui Kan; Qurratu Aini Sirat; Hafsat Omolara Raheem; Adharsh Rajasekar (Hydrology)
Biocementation is an innovative and sustainable technique with wide-ranging applications in slope stabilization, watershed management, and erosion control. Despite its potential, comprehensive evaluations of its use in hydrology and geotechnical engineering are limited. This study addresses this gap through a bibliometric analysis of 685 articles (2013–2023) from the Scopus database, employing VOSviewer and RStudio to explore global research trends, key contributors, and emerging themes. The analysis reveals that China, the United States, and Japan are leading contributors to this field, with significant advancements in microbial-induced (MICP) and enzyme-induced calcium carbonate precipitation (EICP) techniques. These methods have demonstrated effectiveness in improving soil strength, reducing erosion, and enhancing hydrological properties such as infiltration, runoff control, and water retention. Co-occurrence analysis identifies interdisciplinary connections between geotechnics and hydrology, highlighting research clusters focused on biomineralization, erosion resistance, and durability. The findings underscore biocementation’s pivotal role in addressing sustainability challenges by providing environmentally friendly alternatives to traditional soil stabilization techniques. This study not only maps the current research landscape but also offers valuable insights into the practical implications of biocementation for slope stability and hydrological management, laying the foundation for future advancements in sustainable engineering practices.